THE INFLUENCE OF BRAND IMAGE AND BRAND TRUST ON SAMSUNG SMARTPHONE BRAND LOYALTY AMONG MANAGEMENT STUDENTS AT THE FACULTY OF ECONOMICS AND BUSINESS, HALU OLEO UNIVERSITY - Azis Muthalib, Dzulfikri; Wayan Sudasana, I; Masse, Ambo (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to analyze the influence of brand image and brand trust on brand loyalty among Samsung smartphone users who are students of the Management Department, Faculty of Economics and Business, Universitas Halu Oleo Kendari. This research employed a quantitative approach with an explanatory research design. A total of 30 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that brand image and brand trust have a positive and significant effect on brand loyalty, both simultaneously and partially. These findings support recent theories stating that in the digital era, brand loyalty is shaped by the strength and uniqueness of brand associations and consumer trust, which are reinforced through digital interactions and electronic word-of-mouth communication. This research is expected to provide practical insights for companies in designing effective marketing strategies to maintain young consumers’ loyalty in the increasingly competitive smartphone market.